Bilateral Trade Flows, the Linder Hypothesis, and Exchange Risk - Thursby, Jerry G.; Thursby, Marie C. (The Review of Economics and Statistics, 1987)
Bilateral trade flows are used to examine the Linder hypothesis and the effect of exchange-rate variability in a gra vity-type trade model derived from an underlying demand and supply mo del. A behavioral model is used to justify examining these issues joi ntly. The model performs well empirically using a sample of seventeen countries for the period 1974-82. The authors find overwhelming supp ort for the Linder hypothesis and this version of the gravity model. Moreover, they find strong support for the hypothesis that increased exchange-rate variability affects bilateral trade flows. Copyright 1987 by MIT Press.